(Non-)Return of Ukrainian War Refugees: Modeling Repatriation Using Logistic Regression - Сидоров, Микола Володимир-Станіславович; Сальнікова, Світлана Анатоліївна; Северин, Анна (Волинський національний університет імені Лесі Українки, 2024)
Підсумовуючи основні напрями досліджень вимушеної міграції за останні двадцять п’ять років вчені данського незалежного інституту міжнародних досліджень Stepputat and Sørensen (2014) виокремлюють такі, як (1) проблема чіткого розмежування між добровільною та вимушеною міграцією через або нові сфери та процеси, де це розмежування важко провести, або втрату аналітичного сенсу у такому розмежуванні; (2) відсутність теоретичного осмислення та концептуальної складності в галузі досліджень вимушеної міграції; (3) тенденція обмежувати дослідження вимушеної міграції політичними питаннями. Проте, варто зазначити, що теоретичний підхід до вимушеної міграції повинен враховувати глобальний контекст, де політичні та економічні фактори взаємодіють, створюючи умови для масових переміщень людей. Дане дослідження є суголосним означеним напрямам і має на меті побудову прогнозних моделей репатріації українців на основі чинників вимушеної міграції, які знижують рівень їхнього повернення в Україну. Тоді як більшість досліджень спрямовані на вивчення мотивів міграції (van Tubergen et al., 2024), наше дослідження спрямоване на виявлення причин повернення мігрантів, тобто чинників реміграції.

The scale of forced migration of Ukrainians following the full-scale Russian invasion of Ukraine on February 24, 2022, population losses, destruction of infrastructure, and other consequences underscore the importance of addressing the issue of return migration. The return of forced migrants from Ukraine is a significant phenomenon that arises in socio-demographic and economic contexts and requires theoretical revision and conceptual clarification. The purpose of this study is to develop predictive models for the repatriation of Ukrainian war refugees and to evaluate the factors that decrease the likelihood of their return. The authors used the Factum Group dataset, focusing on Ukrainian women who left Ukraine after the full-scale invasion and did not return from emigration, to obtain a sample of forcibly displaced Ukrainian migrant women. Repatriation models were constructed using logistic regression, applied to the overall dataset, and to subsamples from Germany and Poland – countries that received the largest number of Ukrainian war refugees. The assumption that return factors depend on the host country was confirmed. Repatriation models for Germany and Poland demonstrate higher accuracy than the general model and reveal distinct sets of factors influencing the (non-)return of war refugees. In Germany, key factors include the standard of living, availability of work abroad, overall life satisfaction, and prior residence in areas of Ukraine unaffected by active hostilities. For Poland, the significant factors are overall life satisfaction and the intention to return. It was found that not all factors influencing the decision to leave the country – such as region, availability of financial resources, knowledge of a foreign language, and family status – are significant for the decision to return. The repatriation models demonstrate a high level of accuracy in predicting negative cases and moderate accuracy in predicting positive cases, with cases of uncertainty excluded from the regression analysis. These findings confirm that factors related to economic stability, social comfort, and personal intentions are fundamental for predicting the likelihood of (non)return among Ukrainian female migrants.
(Не)повернення українських біженців війни: побудова моделей репатріації засобами логістичної регресії
Keywords: war refugees; forced migration; repatriation model; logistic regression; migration factors; repatriation factors